Fabrication of pesticide/LDH-LAP composite assisted by zwitterionic surfactant - Liu, Jiexiang; Wang, Ping; Hao, Xiang; Zhang, Xiaoguang (Colloids and surfaces. A, Physicochemical and engineering aspects, 2024)
Using zinc-aluminum layered double hydroxides-laponite (LDH-LAP) complex as matrix, with the assistance of zwitterionic surfactants of hexadecyl dimethyl sulfobetaine (SB) and dodecyl dimethyl carboxyl betaine (DCB), the pesticides beta-cypermethrin (BCT) and imidacloprid (IMP) were inserted into the LDH-LAP to obtain BCT/SB-LDH-LAP, BCT/DCB-LDH-LAP, BCT/SB-DCB-LDH-LAP and IMP/DCB-LDH-LAP composites, respectively. Powder X-ray diffraction (XRD), fourier transform infrared spectroscopy (FT-IR), thermogravimetric/differential thermal analysis (TGA/DTA) and scanning electron microscope (SEM) were used to characterize the structural properties of composites. BCT/SB-LDH-LAP, BCT/DCB-LDH-LAP, BCT/SB-DCB-LDH-LAP and IMP/DCB-LDH-LAP had larger interlayer distances of 4.29, 4.33, 4.33 and 4.61 nm, which were bigger than those of SB-LDH-LAP (3.87 nm), DCB-LDH-LAP (3.83 nm) and LDH-LAP (1.65 nm). The FT-IR and TGA/DTA results further confirmed the existence of SB, DCB, BCT and IMP into LDH-LAP. The pesticide releases were investigated and analyzed in pH 5.0 and 6.8 buffer solutions. The release behaviors can be fitted by pseudo second-order and parabolic diffusion models. The composites based on LDH-LAP could be suggested to potential application for controlled-release of the pesticide. [Display omitted]